2019
DOI: 10.1590/1678-4766e2019012
|View full text |Cite
|
Sign up to set email alerts
|

Composição e riqueza de espécies de uma comunidade de Coleoptera (Insecta) na Caatinga

Abstract: RESUMO Os besouros apresentam grande diversidade taxonômica e funcional, no entanto, para a Região Nordeste, especialmente para a porção com vegetação de Caatinga, o conhecimento da fauna de Coleoptera é muito restrito. Por se tratar de uma região com grande diversidade de paisagens, torna-se necessário conhecer a coleopterofauna que ocorre nas diferentes fitofisionomias, buscando com isso abranger a variabilidade espacial encontrada nessa região xérica. Diante disso, o objetivo deste estudo foi realizar um le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…The expressive number of insect families collected in this study was greater than the records obtained for this same taxonomic group in the biomes adjacent to the study area, as shown by the data obtained in the Caatinga by Azevedo et al (2011). The specificity of the collection method used in this study, which includes only the insects that nest in the soil or in the litter, more strongly validates the differences between the number of insect families obtained in this study in relation to other studies with families of insects collected in the Cerrado biome and surroundings, adopting more than one collection method (CAJAIBA et al, 2015;AZEVEDO et al, 2016;POMPEO et al, 2016;GUEDES et al, 2019). The greater number of taxa in the study area was supported by the ecotonal peculiarity of the region, which borders the Pre-Amazon and Caatinga.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The expressive number of insect families collected in this study was greater than the records obtained for this same taxonomic group in the biomes adjacent to the study area, as shown by the data obtained in the Caatinga by Azevedo et al (2011). The specificity of the collection method used in this study, which includes only the insects that nest in the soil or in the litter, more strongly validates the differences between the number of insect families obtained in this study in relation to other studies with families of insects collected in the Cerrado biome and surroundings, adopting more than one collection method (CAJAIBA et al, 2015;AZEVEDO et al, 2016;POMPEO et al, 2016;GUEDES et al, 2019). The greater number of taxa in the study area was supported by the ecotonal peculiarity of the region, which borders the Pre-Amazon and Caatinga.…”
Section: Discussionsupporting
confidence: 77%
“…The predominantly xerophytic climatology of the Cerrados, especially in the central and northeast regions of Brazil, contrasts with the formations of wet forests found on the edges of rivers and springs of this biome. The edaphic fauna of these environments is predominantly composed of insects of the order Coleoptera (AZEVEDO et al, 2016), adapted to soils saturated with water and suitable for the development of aquatic larval phases, such as beetles of the family Dityscidae, which can be found in the adult phase even in xeric environments, as long as there are hydromorphic environments in the surrounding area (GUEDES et al, 2019). The occurrence of insects of the Carabidae and Phoridae families in the four sample sites showed that these insects are possibly affected by other factors that were not evaluated in this study, or this may confirm the resilience and high adaptability of these insects to extreme environments, such as the family fly larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Most specimens were collected using malaise traps standing in the field for at least two consecutive months (Patu and Mossoró-RN), a whole year (Jequié-BA), and four consecutive years (Santa Teresinha-PB) (detailed descriptions of localities and sampling methods were provided in Lucena et al 2012;Zanella and Lucena 2014;Fernandes et al 2014Fernandes et al , 2019Guedes et al 2019). We also examined specimens housed in the following institutions: BME: Bohart Museum of Entomology, University of California, Davis, California, USA (Lynn S. Kimsey; Steven Heydon); DZUP: Coleção Entomológica "Pe.…”
Section: Materials Studiedmentioning
confidence: 99%
“…The characteristics of the exact locations of occurrence are barely presented. Most (Baly 1877, Bowditch 1913, Albertoni 2008, Dias 2016, Guedes et al 2019, Rafael et al 2020 do not provide any information about plants. Only one study reports the presence and collection of immatures.…”
Section: _________________________________________________mentioning
confidence: 99%